Environmental Protection in Ancient Indian Religion System: Exploring the Interconnectedness of Nature and Philosophy in Ancient India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
According to Indian philosophy, the entire universe is created out of the conglomeration of the sub-atomic particles which influence the five gross elements - earth, water, fire, air and space. All living beings, animate or inanimate, come under this classification. So, life forms are created on the backdrop of the gross elements. The five gross elements do inherently carry a link with the five human cognitive organs. The nose carries an inherent relation with the earth, the tongue with the water, the eyes with the fire, the touch with the air and finally, the ear with the space. Hence, a symbiotic relation between macro and micro level environment is apparent in ancient Indian philosophical thought. “These Five Mahabhutas are cosmic elements which create, nurture and sustain all forms of life, and after death or decay they absorb what was created earlier thus they play an important role in preserving and sustaining the environment”